SAT0131 Uric Acid is Associated with Metabolic Syndrome in Longstanding Rheumatoid Arthritis. (9th June 2015) - Agca, R.; van Sijl, A.M.; Voskuyl, A.E.; Nurmohamed, M.T.
Abstract : Background: Cardiovascular (CV) risk is enhanced in patients with rheumatoid arthritis (RA). Metabolic syndrome, a cluster of several classic CV risk factors, has been shown to be more prevalent in patients with RA. Previous studies have associated metabolic syndrome with hyperuricemia, a potential marker for cardiovascular morbidity and mortality. Objectives: To investigate the relationship between uric acid and metabolic syndrome in a prospective observational cohort of longstanding RA patients. Methods: Uric acid was measured in baseline samples of 353 RA patients participating in an ongoing prospective cohort study to assess cardiovascular morbidity and mortality (CARRΈ study). Metabolic syndrome was defined according to the third report of the National Cholesterol Education Program (NCEP) expert panel on detection, evaluation, and treatment of high blood cholesterol in adults (Adult Treatment Panel III, ATP III) (1). Results: 23.8% of the patient in this cohort fulfilled the criteria of metabolic syndrome according to the NCEP ATP III guidelines (1). Patients were predominantly females (65.7%) with a mean age of 63±6 years and a mean RA duration of 8±4 years. Elevated uric acid levels in serum were significantly associated with metabolic syndrome in a univariate analysis (table 1 ). After correction for gender, age, CVD prevalence, RA duration and disease activity in a multivariable model, uric acid remained significantly associated with metabolic syndrome (table 1 ). Conclusions: Elevated serum uric acid levels were significantly associated with metabolic syndrome in patients with longstanding RA. References: Third Report of the National Cholesterol Education Program (NCEP) Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults (Adult Treatment Panel III) final report. Circulation 2002; 106(25):3143-3421. Disclosure of Interest: None declared